Carbon Footprint Principles and Challenges in Transport Logistics - Kenn Steger-Jensen; Hans-Henrik Hvolby; Sven Vestergaard; Mihai Neagoe; Carsten Svensson (Tehnički Glasnik)
Logistic operators are under pressure from consumers and governments to reduce the carbon footprint impact. Operators need increased focus on reducing the carbon impact and calculating their actual carbon emissions. EU's Emissions Trading System comes into force from 2027 and works on the 'cap and trade' principle. A cap is a limit set on the total amount of greenhouse gases that logistic operators may emit. Therefore, there is a need to develop a roadmap and action plans to reduce emissions, which will drastically impact the logistic operators. The paper brings forward current standards, frameworks and principles as well as examples of carbon footprint calculations in last-mile transportation.